2012
DOI: 10.1007/978-3-7091-0956-4_66
|View full text |Cite
|
Sign up to set email alerts
|

Prior Statin Use Has No Effect on Survival After Intracerebral Hemorrhage in a Multiethnic Asian Patient Cohort

Abstract: No beneficial effect on survival after ICH of prior statin use could be demonstrated in our large multi-ethnic Asian patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
1
22
1
1
Order By: Relevance
“…in‐hospital or at 30 or 90 days post‐discharge (OR 0.85, 95% CI 0.70–1.03; Fig. ) . A similar effect was observed when separate analyses were performed for mortality in‐hospital (OR 1.00, 95% CI 0.84–1.20; Fig.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…in‐hospital or at 30 or 90 days post‐discharge (OR 0.85, 95% CI 0.70–1.03; Fig. ) . A similar effect was observed when separate analyses were performed for mortality in‐hospital (OR 1.00, 95% CI 0.84–1.20; Fig.…”
Section: Resultssupporting
confidence: 65%
“…a) and at 30 days (OR 1.04, 95% CI 0.88–1.22; Fig. b) . However, pre‐ICH statin use significantly decreased 90‐day mortality (OR 0.72, 95% CI 0.59–0.88; Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Patients who are treated with statins prior to aSAH tend to have a lower incidence of subsequent CVS (17). However, other studies have shown that simvastatin does not exert a beneficial effect on patients with aSAH (8,9). Kramer et al (11) pointed out that if there is a benefit to statin use, it may be smaller than suggested by previous studies.…”
Section: Introductionmentioning
confidence: 97%